Mechanoregulatory role of TRPV4 in prenatal skeletal development - Hoey, David (My University, 2023)
Biophysical cues are essential for guiding skeletal development, but the mechanisms underlying the mechanical regulation of cartilage and bone formation are unknown. TRPV4 is a mechanically sensitive ion channel involved in cartilage and bone cell mechanosensing, mutations of which lead to skeletal developmental pathologies. We tested the hypothesis that loading-driven prenatal skeletal development is dependent on TRPV4 activity. We first establish that mechanically stimulating mouse embryo hindlimbs cultured ex vivo stimulates knee cartilage growth, morphogenesis, and expression of TRPV4, which localizes to areas of high biophysical stimuli. We then demonstrate that loading-driven joint cartilage growth and shape are dependent on TRPV4 activity, mediated via control of cell proliferation and matrix biosynthesis, indicating a mechanism by which mechanical loading could direct growth and morphogenesis during joint formation. We conclude that mechanoregulatory pathways initiated by TRPV4 guide skeletal development; therefore, TRPV4 is a valuable target for the development of skeletal regenerative and repair strategies.
PUBLISHED
Keywords: Biochemistry; Bone; Cartilage; Joints; Next Generation Medical Devices; Bioengineering